Increased Rostral Anterior Cingulate Cortex Volume in Chronic Primary Insomnia - Winkelman, John W. (Associated Professional Sleep Societies, LLC, 2013)
BACKGROUND: Recent studies document alterations in cortical and subcortical volumes in patients with chronic primary insomnia (PI) in comparison with normal sleepers. We sought to confirm this observation in two previously studied PI cohorts. METHODS: Two separate and independent groups of unmedicated patients who met Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition (DSM-IV) criteria for PI were compared with two separate, healthy control groups (Study 1: PI = 20, controls = 15; Study 2: PI = 21, controls = 20). Both studies included 2 weeks of sleep diaries supplemented by wrist actigraphy. The 3.0 T MRI-derived rostral anterior cingulate cortex (rACC) volumes were measured with FreeSurfer image analysis suite (version 5.0) and results normalized to total intracranial volume (ICV). Unpaired t-tests (two-tailed) were used to compare rACC volumes between groups. Post hoc correlations of rACC volumes to insomnia severity measures were performed (uncorrected for multiplicity). RESULTS: Both studies demonstrated increases in normalized rACC volume in PI compared with control patients (Study 1: right side P = 0.05, left side P = 0.03; Study 2: right side P = 0.03, left side P = 0.02). In PI patients from Study 1, right rACC volume was correlated with sleep onset latency (SOL) by both diary (r = 0.51, P = 0.02) and actigraphy (r = 0.50, P = 0.03), and with sleep efficiency by actigraphy (r = -0.57, P = 0.01); left rACC volume was correlated with SOL by diary (r = 0.48, P = 0.04), and wake after sleep onset (WASO) (r = 0.49, P = 0.03) and sleep efficiency (r = -0.49, P = 0.03) by actigraphy. In Study 2, right rACC volume was correlated with SOL by diary (r = 0.44, P = 0.05) in PI patients. CONCLUSIONS: Rostral ACC volumes are larger in patients with PI compared with control patients. Clinical severity measures in PI correlate with rACC volumes. These data may reflect a compensatory brain response to chronic insomnia and may represent a marker of resilience to depressive illness. CITATION: Winkelman JW; Plante DT; Schoerning L; Benson K; Buxton OM; O'Connor SP; Jensen JE; Renshaw PF; Gonenc A. Increased rostral anterior cingulate cortex volume in chronic primary insomnia. SLEEP 2013;36(7):991-998.